2017
DOI: 10.1186/s12879-017-2251-x
|View full text |Cite
|
Sign up to set email alerts
|

Suspicion of respiratory tract infection with multidrug-resistant Enterobacteriaceae: epidemiology and risk factors from a Paediatric Intensive Care Unit

Abstract: BackgroundMultidrug-resistant (MDR) infections are a serious concern for children admitted to the Paediatric Intensive Care Unit (PICU). Tracheal colonization with MDR Enterobacteriaceae predisposes to respiratory infection, but underlying risk factors are poorly understood. This study aims to determine the incidence of children with suspected infection during mechanical ventilation and analyses risk factors for the finding of MDR Enterobacteriaceae in tracheal aspirates.MethodsA retrospective single-centre an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
(37 reference statements)
3
12
0
Order By: Relevance
“…As colonization of an endotracheal tube occurs quickly, the mere presence of bacteria in surveillance cultures from endotracheal aspirates does not warrant antibiotic treatment [75]. Of note, > 30% of Enterobacterales in endotracheal aspirates may be MDR, with a clear link to previous antibiotic exposure of > 7 days [76]. Studies in adults revealed that only very recent cultures (from endotracheal aspirates taken ≤ 2 days before onset of VAP) are reliable in predicting the responsible pathogen [77].…”
Section: Hospital-acquired Infections In the Picumentioning
confidence: 99%
“…As colonization of an endotracheal tube occurs quickly, the mere presence of bacteria in surveillance cultures from endotracheal aspirates does not warrant antibiotic treatment [75]. Of note, > 30% of Enterobacterales in endotracheal aspirates may be MDR, with a clear link to previous antibiotic exposure of > 7 days [76]. Studies in adults revealed that only very recent cultures (from endotracheal aspirates taken ≤ 2 days before onset of VAP) are reliable in predicting the responsible pathogen [77].…”
Section: Hospital-acquired Infections In the Picumentioning
confidence: 99%
“…The articles included in this review were all observational studies: 12 were cohort studies (7 retrospective studies [19][20][21][22][23][24] and 5 prospective studies [25][26][27][28][29] ) and 17 were case-control studies. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] The study sample for all articles were hospitalized children, although their ages differed among the studies.…”
Section: Study Designs Sample and Association Between Antibiotic Usmentioning
confidence: 99%
“…Seven studies included specific age ranges, 20,23,25,27,30,41,42 10 studies included only neonates, 19,21,24,26,28,29,32,37,38,47 and 12 studies did not provide an age range for the children included. 22,31,[33][34][35][36]39,40,[43][44][45][46] Organisms included in the articles were Enterobacteriaceae (n = 10), 19,22,26,35,36,[41][42][43][44][45] Klebsiella pneumoniae (n = 8), 21,23,27,28,34,38,46,47 Escherichia coli (n = 5), 23,33,37,46...…”
Section: Study Designs Sample and Association Between Antibiotic Usmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of literature regarding factors associated with high-risk GNRs in children and no statistical models that predict increased risk for these pathogens [ 17 , 18 ]. Such a model could aid in the development and testing of empirical antimicrobial prescribing strategies in critically ill children.…”
mentioning
confidence: 99%